وسيلة وسيلة وورد وال لتعليم فهم المعنى المفردات العربية في مدرسة المتوسطة الإسلامية الحكومية واحد بميكاسان - Dusturia, Nida Dusturia (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2022)
ملخص في عصر الرقمنة، مهم جدا أن يعرف المعلم التكنولوجيا ويتقنوها ثم ينفذونها في عملية التعليم لتكون فعالة. وسيلة وورد وال هي وسيلة قائم على الويب التي يستخدمه ليجعل التعليم أكثر متعة، بالإضافة إلى وسيلة تعليمية للحفاظ على نشاط الطلاب في التعليم. أهداف هذه البحث هي: (1) لمعرفة فعالية وسيلة وورد وال في تعليم فهم معنى المفردات العربية. استخدم هذا البحث نوعا من البحث شبه التجريبية مع نوع الاختبار قبلي البعدي لتصميم المجموعة الضابطة غير المكافئة ويستخدم عينة هي 52 طالبا. تقنيات جمع البيانات هي المقابلة والملاحظة والاختبارات (الاختبار القبلي والبعدي) والتوثيق. أما بالنسبة لتقنية تحليل البيانات باستخدام اختبار الحالة الطبيعية واختبار التجانس واختبار Mann Whitney واختبار الفرضية باستخدام اختبار N-Gain المعالج باستخدام SPSS 20 . نتائج هذه البحث هي 1) وسيلة وورد وال فعالة في تعليم فهم المفردات العربية مع اختبار N-Gain، والدرجة متوسطة التي حصلت عليها المجموعة التجريبية أعلى 79.00 من المجموعة الضابطة التي تبلغ 36.21. وإما في نتائج الفرضية باستخدام اختبار Mann Whitneyحصلت على نتيجة قيمة sig 0،05 < 0،001لتعليم فهم المعنى. لذلك من خلال التعرض أعلاه Ho تم مرفوض و Ha تم مقبول. استنتاجها أن وسيلة وورد وال فعالة في تعليم النطق وفهم المعنى تكوين الجملة في المفردات العربية لطلاب الصف السابع "ج" في مدرسة المتوسطة الإسلامية الحكومية واحد بميكاسان. ABSTRACT In the age of digitisation, educators are very important to know and master technologies and be implemented in the learning process to be effective. The wordwall application is a web-based application that can be used to make learning more enjoyable, as well as a learning medium to keep students active in learning. The purpose of the research is: (1) to find out how it affects the wordwall application in understanding the meaning of the Arabic vocabulary. This research use the type of experimental quasi research with the non-invasive control type design and sample uses 52 students. The data-gathering techniques used are interviews, observations, tests (those of pre-test and post-test), and documentaries. Whereas for data analysis techniques using normality tests and homogenization tests Mann Whitney tests and hypothetical tests using N-Gain using a SPSS 20 for Windows. The study showed that 1) wordwall application is effective in understanding the meaning of the Arabic vocabulary with n-gain tests, mean the score obtained by the experimental group is 79% higher than the control class of 36%. While hypotheses using the Mann Whitney test results in sig. 0,001<0,05 for Understanding of meaning the Arabic vocabulary. So from the foregoing it can be concluded that wordwall application is effective in Understanding of meaning the Arabic vocabulary class VII C Junior Islamic high school 1 Pamekasan.